Constantine the Emperor - Potter, D. S., 1957-, (Oxford University Press, 2013)
With a critical eye aimed at earlier accounts of Constantine's life, the author aims to provide the most comprehensive, authoritative and readable account of the Roman emperor's extraordinary life.